A Sustainability-Based Occupational Safety Risk Prioritization Model for High-Rise Building Maintenance Using HIRARC and AHP - Emma Budi Sulistiarini; Evi Yuliawati; Diky Siswanto; Bambang Suhardi; M. Ashlyzan Bin Razik (JTI: Jurnal Teknik Industri, 2026)
High-rise building maintenance involving work at height presents significant occupational safety risks, particularly fall-related incidents that may result in severe injuries, operational disruptions, and financial losses. Conventional risk assessment approaches such as Hazard Identification, Risk Assessment, and Risk Control (HIRARC) primarily rely on technical likelihood–severity scoring and do not explicitly incorporate sustainability consequences into risk prioritization. This study develops a sustainability-based occupational safety risk prioritization model for high-rise building maintenance by introducing a Sustainability Risk Priority Index (SRPI) that integrates HIRARC-based technical risk scores, Triple Bottom Line (TBL) weighting derived from the Analytic Hierarchy Process (AHP), and hazard-level sustainability impact assessment. Unlike conventional approaches that prioritize hazards primarily based on technical risk magnitude, the proposed SRPI provides a composite prioritization framework that also captures People, Planet, and Profit consequences in measurable terms. The model was demonstrated through a case study of a three-story laboratory building that identified six hazards. The results show that falls from the rooftop edge and falls from a narrow canopy platform remain the highest technical risks (R = 20). The AHP weighting yielded People = 0.60, Profit = 0.25, and Planet = 0.15, with a Consistency Ratio (CR) of 0.07. The proposed model differentiates medium-level hazards more clearly by incorporating sustainability consequences while preserving the dominance of hazards with potentially fatal outcomes. Sensitivity analysis with ±10% variation in the People weight indicates that the highest-priority hazards remain stable across scenarios. Keywords: Occupational safety; Sustainability risk prioritization; HIRARC; AHP; High-rise building maintenance